Denervasi Ginjal: Suatu Terapi Tambahan Hipertensi Resisten - Laksono, Sidhi (Majalah Kedokteran Indonesia, 2025)
Hypertension is one of the major risk factors for cardiovascular disease worldwide. Evidence has demonstrated that effective blood pressure control can reduce cardiovascular morbidity and mortality while slowing the progression toward end-stage renal disease. However, blood pressure control rates in the global population remain far from optimal despite the availability of various lifestyle-based and pharmacological treatment options. Recent data indicate that among approximately 120 million adults with hypertension in the United States, only about 23% have successfully achieved the target blood pressure of kess then 130/80 mmHg, whereas nearly 45% continue to have blood pressure levels ≥140/90 mmHg.